Evaluasi Perubahan Susunan Gigi Anterior Bawah Pasca Perawatan Ortodonti Menggunakan Irregularity Index (Kajian model studi pada pasien klinik ortodonti RSGM FKG UI) - Eveline Hartanto; Nia Ayu Ismaniati; Krisnawati Krisnawati (Journal of Dentistry Indonesia, 2015)
The purpose of this study was to evaluate relapse on mandibular anterior teeth after orthodontic treatment using irregularity index. In total 44 subjects were included, 10 men and 34 women, aged 15 to 37 years. All patients wore Hawley retainers. The results showed that there were statistically significant differences between the values of irregularity index at the completion of orthodontic therapy (mean ii T2 = 0.57 mm) and in the retention periods (mean ii T3 = 2.36 mm). The changes of mandibular anterior teeth irregularity were in the minimal category for the majority of cases.